How does the maturation state of cardoon bracts influence its phenolic composition and bioactivity? - Mandim, Filipa (2022)
Cynara cardunculus L. (cardoon) is an herbaceous plant native to the Mediterranean basin. It is widely used due to its nutritional, pharmacological, and industrial applications [1]. Besides its consumption in various recipes, due to its rich nutritional composition and health-promoting effects, it is also widely used in several industry sectors (e.g., cheese manufacturing, and in the production of pharmaceuticals, bioenergy, and biomass). Its multiple applications are extremely important for the enhancement of the species‘ added value [2]. However, factors such as genetic information, plant tissue, and maturity state can influence the potential of the species [1,2]. The study of the influence of all these variables is extremely important for its proper use, as well for its economic valorisation. Cardoon bracts were collected in Greece at eight harvesting dates (Principal Growth Stage between 5 and 8/9). The phenolic composition of their hydroethanolic extracts was analysed by HPLC-DAD-ESI/MS. The antioxidant activity was evaluated with two cell-based assays: thiobarbituric acid reactive substances (TBARS) formation inhibition and oxidative haemolysis assay (OxHLIA). The anti-inflammatory activity was evaluated by determining the extracts‘ ability to inhibit nitric oxide production in a murine macrophage cell line. Finally, cytotoxicity was assessed against four human tumour cell lines and a porcine liver primary cell culture using the sulforhodamine B assay. Twelve phenolic compounds were tentatively identified, with 3,5-O-dicaffeoylquinic acid and apigenin-7-O-glucuronide being the major compounds detected. Immature bracts presented the highest phenolic compounds content, as also the highest anti-inflammatory and cytotoxic activities. Regarding the antioxidant activity, immature bracts revealed the highest ability to inhibit the formation of TBARS. For OxHLIA, cardoon bracts harvested at more advanced maturation stages were the ones that revealed the highest activity. In conclusion, it was verified that the maturation stage influences the phenolic composition and the biological potential of cardoon bracts. However, more studies are needed to understand and correlate the compounds responsible with the observed bioactivities.